Confessions of an economic hit man - Perkins, John 1945- (A BK currents book, 2004)
Perkins, a former chief economist at a Boston strategic-consulting firm, confesses he was an "economic hit man" for 10 years, helping U.S. intelligence agencies and multinationals cajole and blackmail foreign leaders into serving U.S. foreign policy and awarding lucrative contracts to American business